Evaluation of red currant varieties according to productivity and marketability - O. D. Golyaeva (Аграрная наука Евро-Северо-Востока, 2024)
The purpose of the research is to study the yield and the main components of the productivity of 9 red currant cultivars of early and medium maturation from the bioresource collection of the Russian Research Institute of Fruit Crop Breeding and to assess the degree of stability of the traits. The study was carried out in 2020, 2022, 2023 in the Orel region. The collection plot was laid in autumn 2015 according to the scheme 3.5 x 0.5 m. In the studied cultivars, the raceme length varied significantly over the years from 20.0 % (‘Vika’) to 35.6 % (‘Krasnaya Kuzmina’), depending on the meteorological conditions of the growing season. On average, over the years of study, the raceme length of the control ‘Jonkheer van Tets’ cultivar was 8.6 cm, and only the ‘Krasnaya Kuzmina’ cultivar had significant differences from the control in raceme length – 10.9 cm. The ‘Niva’ cultivar showed large fruit, the average berry weight for three years was 0.76 g and significantly exceeded the control cultivar (0.54 g). The rest cultivars were included in the group with an average berry weight. The values of the berry weight varied greatly over the years. The variation coefficient (CV) ranged from 8.4 % (‘Jonkheer van Tets’) to 31.7 % (‘Niva’). The cultivars ‘Natalie’ and ‘Vika’ were characterized by the uniformity of the berries in the raceme. On average, over 3 years, the cultivars showed high yields from 14.3 t/ha in ‘Red Cross’ (CV 48.7 %) to 25.6 t/ha in ‘Gazel’ (CV 10.7 %). ‘Gazel’, ‘Asya’ and ‘Podarok Pobeditelyam’ were distinguished by high stable yields and parameters of productivity components. ‘Niva’ was characterized by large size of fruit and high yield, but it had less stability over the years. ‘Red Cross’ did not realize its genetic productivity potential in the conditions of the Orel region.